High and Low Temperature Properties of FT-Paraffin-Modified Bitumen - Hassan Fazaeli; Hamid Behbahani; Amir Ali Amini; Jafar Rahmani; Golazin Yadollahi (Advances in Materials Science and Engineering)
This paper presents the results of an experimental research on the effects of “Fischer Tropsch-Paraffin” (Sasobit) content on physical and rheological properties of Sasobit modified bitumen at various operational temperatures. For this purpose, bitumen with a Performance Grade (PG) of 58–22 is selected as the base and later it is modified with 1, 2, 2.5, 3, and 4 weight percent of FT-Paraffin (Sasobit). The performance of modified bitumen at high, intermediate, and low temperatures is evaluated based on Strategic Highway Research Program (SHRP) Superpave tests. Results of the study show that FT-paraffin improves the performance of bitumen at high temperatures in addition to increasing the resistance of mixture against permanent deformation. Despite the advantages of FT-paraffin on bitumen performance at high temperatures, it does not show a considerable influence on the intermediate and low temperature performance of bitumen. The effect of FT-paraffin content on the viscosity of modified bitumen is also investigated using Brookfield Viscometer Apparatus. Results show that increasing the additive content lowers the viscosity of modified bitumen. This in return can reduce the mixing and compaction temperature of asphalt mixtures.